Knowledge, Attitude, and Practice towards Glycemic Control and Its Associated Factors among Diabetes Mellitus Patients - Daniel Asmelash; Netsanet Abdu; Samson Tefera; Habtamu Wondifraw Baynes; Cherie Derbew (Journal of Diabetes Research)
Background. Diabetes mellitus is a metabolic disorder of multiple etiologic factors characterized by chronic hyperglycemia with disturbance of carbohydrate metabolism. It can play the vital role in the cause of morbidity and mortality through continued clinical consequence. Therefore, good knowledge, attitude, and practices of glycemic control are necessary in promoting care, in enhancing better therapeutic outcomes, and in the prevention and management of diabetes complications. Methods. A cross-sectional study design was conducted to determine knowledge, attitude, and practice towards glycemic control and its associated factors. Diabetic patients who were attending the University of Gondar Hospital from March to May 2018 were included in the study. The data was collected using questionnaires, and individuals that can fulfill our inclusion criteria were selected by a simple random sampling technique. SPSS version 20 was used for descriptive and logistic regression analysis, and finally, the variables were summarized and presented using tables and graphs. Results. Of the total 403 participants, 216 (53.6%) were males and 176 (43.7%) were illiterate. Of the total, 250 (62%) had good knowledge, 271 (67.2%) had a good attitude, and 300 (74.4%) had good practice towards glycemic control. In multivariate logistic regression, occupational status and marital status were significantly associated with the knowledge of participants towards glycemic control. Occupational status, educational status, and marital status were significantly associated with attitude and practice towards glycemic control. Conclusion. More than half of the participants had good knowledge, attitude, and practice towards glycemic control. Occupational status and marital status were significantly associated with knowledge, attitude, and practice towards glycemic control.